Unregulated Orthodontic Practice and Its Implications for Equity and Sustainability in Public Health - Himmaturojuli Rosyid Ridlo; Retno Mawarini Sukmariningsi; Inge Hartini; Clarizze Yvoine Mirielle (Journal of Sustainable Development and Regulatory Issues (JSDERI), 2026)
Fixed orthodontic treatment improves oral function, dental aesthetics, and malocclusion correction within dental health services. Patients frequently select general dentists because they offer affordable and accessible treatment. However, the absence of comprehensive regulations governing the authority of general dentists in fixed orthodontic procedures creates legal uncertainty and increases potential risks to patient safety. This study examines the regulation of fixed orthodontic services provided by general dentists, identifies factors that hinder the improvement of public health outcomes, and evaluates the urgency of strengthening legal regulations governing fixed orthodontic treatment. The research applies an empirical normative legal method by using secondary legal materials as primary data and primary field data as supporting evidence. The study further analyzes statutory regulations concerning the authority of general dentists in fixed orthodontic practice and assesses their implementation within dental health services. The findings demonstrate that first, orthodontic treatment in Indonesia is generally regulated as a specialized service requiring specific professional competence, although existing regulations have not fully met the public’s need for affordable and accessible care. Second, the limited number and unequal distribution of orthodontic specialists, high treatment costs, and low public awareness regarding professional competence encourage many patients to seek treatment from general dentists. Third, these conditions create legal, ethical, and professional challenges, thereby requiring adaptive regulatory reforms through competency-based training, stricter supervision, and stronger collaboration among the government, professional organizations, and educational institutions to ensure safe, equitable, and high-quality orthodontic services in Indonesia.